Curriculum Development Management: The Key to Improving The Quality of Education in High School - Sumarsi; Samsul Arifin; Zainor Rahman; M. Kurma Nur Faifatur R (Jurnal Manajemen Pendidikan Islam Darussalam, 2025)
This study aims to analyze curriculum development management in an effort to improve the quality of education at SMA Negeri 4 Raja Ampat. The focus of this study includes planning, implementation, evaluation, and obstacles faced in curriculum development. The research approach used is qualitative with a case study design. Data collection techniques through observation, interviews, and documentation. The research subjects consisted of madrasah principals, teachers, and education personnel. The results of the study indicate that curriculum development planning at SMA Negeri 4 Raja Ampat includes routine activities such as monthly KKG/KKM, annual training and seminars, and in-house training. All of these activities are integrated in the RKM and RKAM, which include learning strategies, guidance, assessment, and financing, and serve as guidelines for curriculum implementation. The implementation of the curriculum in the classroom involves a syllabus that integrates character values, detailed RPP, and extracurricular activities to develop student talents. Evaluation is carried out with continuous monitoring to identify obstacles, as well as assessments to measure success and provide improvement solutions, with internal and external supervision throughout the process.